The Composite Face Effect Between Young and Older Chinese Adults Remains Stable - Zhang, Lina; Yang, Qi; Sommer, Werner; Chen, Changming; Guo, Guiting; Cao, Xiaohua (Frontiers in Psychology, 2021)
Holistic face perception is often considered to be a cornerstone of face processing. However, the development of the ability to holistically perceive faces in East Asian individuals is unclear. Therefore, we measured and compared holistic face processing in groups of Chinese children, young adults, and older adults by employing the complete composite face paradigm. The results demonstrate a similar magnitude of the composite effect in all three groups although face recognition performance in the task was better in young adults than in the two other groups. These findings suggest that holistic face perception in Eastern individuals is stable from late childhood to at least age 60, whereas face memory may be subject to later development and earlier decline.